Case report: A novel homozygous variant in ZP3 is associated with human empty follicle syndrome - Kong, Na; Xu, Qian; Shen, Xiaoyue; Zhu, Xiangyu; Cao, Guangyi (Frontiers in Genetics, 2023)
Empty follicle syndrome (EFS) is a rare condition in female infertility. It is characterized by the inability to retrieve oocytes from visibly large, normally developing follicles in the ovaries, despite ovarian stimulation. The genetic factors contributing to this syndrome remain unclear. This study focused on patients who underwent three consecutive ovarian stimulation procedures for oocyte retrieval but experienced unsuccessful outcomes, despite the presence of observable large follicles. Ultrasound examinations were conducted to assess follicular development during each procedure. In order to investigate potential genetic causes, we performed whole exome sequencing on peripheral blood samples from the patient. Interestingly, we identified that this patient carries a homozygous mutation in the ZP3 genes. Within the ZP3 gene, we identified a homozygous variant [NM_001110354.2, c.176T>A (p.L59H)] specifically located in the zona pellucida (ZP) domain. Further analysis, including bioinformatics methods and protein structure modeling, was carried out to investigate the conservation of the ZP3L59H variant across different species. This homozygous variant exhibited a high degree of conservation across various species. Importantly, the homozygous ZP3L59H variant was associated with the occurrence of empty follicle syndrome in affected female patients. The homozygous ZP3L59H variant represents a newly discovered genetic locus implicated in the development of human empty follicle syndrome. Our findings contribute to a deeper understanding of the role of zona pellucida-related genes in infertility and provide valuable insights for the genetic diagnosis of female infertility.